Composite positive electrode material containing high-lithium manganese-based material, electrode sheet, preparation method and application

CN122950445APending Publication Date: 2026-10-20INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182184.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

本申请提供的复合正极材料能够有效解决现有正极材料比容量发挥不足以及传统补锂剂反应产物导致正极比容量下降的问题

Benefits of technology

[0022]当高锂锰基材料具有O2相和/或O3相单晶结构且其中值粒径D50为1~5 μm、主体正极活性物质的中值粒径D50为8~20 μm时,两者还能够形成大小颗粒的粒径级配。较小粒径的高锂锰基材料能够填充于较大粒径的主体正极活性物质颗粒之间,从而提高复合正极材料的堆积密度和极片压实密度,并减少高锂锰基材料与电解液或电解质的直接接触面积,有利于抑制界面副反应,提高复合正极材料的循环稳定性和安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a composite cathode material containing a high-lithium manganese-based material, an electrode sheet, a preparation method, and applications. The composite cathode material comprises: a high-lithium manganese-based material and a cathode active material; the chemical structural formula of the high-lithium manganese-based material is Li. m Li 1+x1 Ni y1 Co z1 Mn 1‑x1‑y1‑ z1 O2; where m ranges from 0.2 to 1.1, x1 ranges from 0.1 to 0.3, m+x1 ranges from 0.5 to 1.2, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2; where, by Li m The additional lithium-intercalated lithium-rich manganese-based host material Li represents the addition of lithium intercalation. 1+ x1 Ni y1 Co z1 Mn 1‑x1‑y1‑z1 The O2 crystal lattice occupies tetrahedral sites in the lattice of the lithium-rich manganese-based host material; the high-lithium manganese-based material accounts for 10-30 wt% of the composite cathode material; the high-lithium manganese-based material is used to release at least part of the additionally introduced lithium during the first charge and convert it into an electrochemically active lithium-rich manganese-based material, which is used to continuously participate in reversible lithium insertion and delithiation reactions during subsequent charge and discharge cycles, and at least part of the released lithium is used to compensate for irreversible lithium loss during the first charge and discharge cycle of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, and in particular to a composite cathode material containing high lithium manganese-based materials, an electrode sheet, a preparation method, and an application. Background Technology

[0002] With the rapid development of new energy vehicles, high-end portable electronic devices, and large-scale energy storage systems, the market has placed increasingly stringent demands on the energy density, cycle life, and safety performance of lithium-ion batteries. As the core component of lithium-ion batteries, the performance of cathode materials directly determines the upper limit of the battery's energy density and cost, making it a key breakthrough for industrial technology upgrades.

[0003] Currently, commercially available lithium-ion battery cathode materials mainly include lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), and ternary materials (LiNi). 1-X-y Co x Mn y O2, LiNi 1-x-y Co x Al y (O2), etc. The cathode material has a decisive influence on the capacity of lithium-ion batteries. Its chemical composition and crystal structure directly determine the number of lithium ions that can participate in cycling, as well as the efficiency and stability of lithium-ion insertion / extraction. In current mainstream battery systems, the specific capacity, structural stability, and interfacial reaction characteristics of the cathode material are the core factors restricting battery energy density and cycle life.

[0004] On the one hand, limitations in the actual specific capacity of cathode materials and cycle performance make it difficult to improve the energy density of battery systems. For example, the theoretical specific capacity of lithium cobalt oxide (LCO) is about 274 mAh / g, but in practice it can only achieve 150-170 mAh / g. The upper limit of the operating voltage of commercially available LCO-based batteries is about 4.35V. Further increasing the charging cutoff voltage, for example, to above 4.5V (vs. Li...), further challenges exist. + When lithium-ion batteries are charged with lithium-manganese (Li), problems such as decreased structural stability, intensified interfacial side reactions, and increased risk of thermal runaway tend to arise, thus limiting further improvements in energy density. Developing higher-capacity cathode materials is a crucial current research direction. Lithium-rich manganese-based cathode materials (LRM) are considered one of the most promising candidates for next-generation high-energy-density lithium-ion batteries. Upon initial charging to high voltage, this material can release additional lithium ions and activate lattice oxygen redox reactions through an "activation" process, achieving an ultra-high reversible specific capacity greater than 250 mAh / g, with a theoretical energy density significantly higher than many existing commercial cathode materials. However, this material still faces numerous challenges in practical applications, mainly including low initial coulombic efficiency, voltage hysteresis, significant voltage decay, and poor safety, severely hindering its commercialization.

[0005] On the other hand, in a full-cell battery system, the consumption of active lithium during the first charging cycle of a lithium-ion battery directly leads to a decrease in initial coulombic efficiency and initial capacity loss. Specifically, an irreversible reduction reaction occurs on the surface of the negative electrode, forming a stable solid electrolyte interphase (SEI) film. This process consumes a large number of lithium ions, which cannot participate in subsequent cycles, resulting in permanent loss of active lithium. Currently used graphite and silicon-based negative electrodes exhibit particularly high lithium consumption, especially silicon-based negative electrodes due to their large volume expansion and continuous SEI film regeneration. Furthermore, the specific capacity of the positive electrode material decreases during cycling, fundamentally due to the irreversible evolution of the material's microstructure and the continuous occurrence of interfacial side reactions, leading to the continuous loss of active lithium ions and intercalation / deintercalation sites. To address the problem of low initial coulombic efficiency and decreased reversible capacity during cycling caused by the large consumption of active lithium on the negative electrode side to form the SEI film in the first cycle, the industry has adopted the method of adding "lithium replenishing agents" to the positive electrode formulation to compensate for the irreversible loss of active lithium. Cathode lithium replenishers are typically sacrificial materials, meaning they release lithium ions during the first charge of the battery, and the products after lithium ion release are generally electrochemically inert, thus "sacrificing" themselves to provide additional lithium. For example, a typical lithium replenisher, Li5FeO4, has a theoretical lithium replenishment capacity as high as 700 mAh / g, and can be used at approximately 4.0 V (vs. Li). + Lithium delithiation occurs within the voltage range of Li, forming reaction products such as iron-containing oxides and lithium-containing oxides. However, Li5FeO4 has extremely poor electronic conductivity, requiring a large amount of conductive agent when added to the positive electrode, and its decomposition products are insulators, occupying positive electrode space without contributing capacity. Lithium supplementers such as Li2O and Li2O2 have extremely high theoretical lithium supplementation capacity, but they are chemically extremely reactive, unstable in air, and highly reactive with slurry solvents (NMP) and water, resulting in extremely poor process compatibility. Other positive electrode lithium supplementers (such as Li2S and Li3N) have similar problems, such as gas generation (H2S, NH3), voltage platform mismatch, and harmful products.

[0006] Currently, research on the three key technologies of cathode material modification, new material system development, and cathode lithium replenishment technology is still being conducted in parallel, lacking an integrated and synergistic design approach based on the "whole battery system." Existing technologies typically treat these three as modules that can be independently optimized and then physically combined: 1) focusing on improving the structural stability of cathode materials such as LCO under high voltage, using them as carriers for high voltage and high specific capacity; 2) exploring high-specific-capacity materials such as LRM, developing cathode materials or forming composite cathodes through simple physical mixing with other cathode materials such as LCO, but still struggling to improve the actual energy density of the battery in practical applications; 3) treating lithium replenishment technology (such as adding sacrificial additives like Li5FeO4) as an independent "external" functional unit to compensate for system lithium loss, but ignoring the negative impact of the lithium replenishment agent, namely the energy density decrease caused by the lithium replenishment agent products occupying electrode space. Therefore, the independent operation of each technology module fails to achieve functional complementarity, and even simple combination of the three may result in the overall system performance not being fully realized due to a lack of synergistic matching between components.

[0007] In summary, due to the limitations of existing cathode materials and the fact that the products of the initial charging reaction of existing cathode lithium replenishment agents become harmful or useless "dead mass" that remains in the cathode for a long time, the overall energy density of the electrode is continuously "diluted" during cycling. These factors together limit the further improvement of the specific capacity and energy density of existing cathode materials and may lead to the inability to fully utilize the effective capacity of the cathode. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of existing technologies by providing a composite cathode material, electrode sheet, preparation method, and application containing high-lithium manganese-based materials. The composite cathode material provided in this application effectively solves the problems of insufficient specific capacity utilization in existing cathode materials and the decrease in specific capacity caused by the reaction products of traditional lithium replenishment agents. The excess lithium contained in the high-lithium manganese-based material in the composite cathode material fully exerts its lithium replenishment function during the first charge, compensating for the irreversible loss of active lithium in the battery system. Simultaneously, after releasing excess lithium, the high-lithium manganese-based material transforms into electrochemically active lithium-rich manganese-based products. These lithium-rich manganese-based products complement the main cathode active material in the composite cathode material, and synergistically participate in reversible electrochemical reactions as cathode active materials during subsequent charge-discharge cycles. This improves the first-cycle charge capacity and post-formation cycle capacity of the battery system, and further enhances the battery's specific capacity, energy density, cycle performance, and safety performance.

[0009] To achieve the above objectives, in a first aspect, the present invention provides a composite cathode material containing a high-lithium manganese-based material, comprising: a high-lithium manganese-based material and a cathode active material; The chemical structural formula of the high-lithium manganese-based material is Li m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where m ranges from 0.2 to 1.1, x1 ranges from 0.1 to 0.3, m+x1 ranges from 0.5 to 1.2, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2; Among them, Li m The additional lithium-intercalated lithium-rich manganese-based host material Li represents the addition of lithium intercalation. 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2 occupies tetrahedral sites in the crystal lattice of the lithium-rich manganese-based host material; The high-lithium manganese-based material accounts for 10-30 wt% of the mass percentage of the composite cathode material; The high-lithium manganese-based material is used to release at least part of the Li during the first charge. m The additional lithium introduced is converted into an electrochemically active lithium-rich manganese-based material to continuously participate in reversible lithium insertion and delithiation reactions during subsequent charge-discharge cycles, and at least a portion of the released lithium is used to compensate for irreversible lithium loss during the first charge-discharge cycle of the battery.

[0010] Preferably, in the chemical structural formula of the high-lithium manganese-based material, m ranges from 0.4 to 0.8, x1 ranges from 0.2 to 0.3, m+x1 ranges from 0.6 to 1.1, y1 ranges from 0.02 to 0.15, and z1 ranges from 0.03 to 0.15; The high-lithium manganese-based material accounts for 15-25 wt% of the mass of the composite cathode material.

[0011] Preferably, the high-lithium manganese-based material is: micron-sized pure phase particles with a single crystal structure of O2 phase and / or O3 phase and a median particle size D50 of 1 to 5 μm; The median particle size D50 of the positive electrode active material is 8–20 μm.

[0012] Preferably, the positive electrode active material includes: LiCoO2, LiNi a Mn 2-a O4 or ternary material LiNi 1-x-y Co x M y One or more of O2; Among them, LiNi a Mn 2-a In O4, 0 ≤ a ≤ 0.5; LiNi1-x-y Co x M y In O2, M is either Mn or Al, 0 < x < 0.5, 0 < y < 0.5, and x + y ≤ 0.5.

[0013] Secondly, embodiments of the present invention provide a method for preparing the composite cathode material described in the first aspect above, comprising: Preparation or preparation of lithium-rich manganese-based materials Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where x1 ranges from 0.1 to 0.3, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2; Lithium supplementation is performed on the lithium-rich manganese-based material to obtain a high-lithium manganese-based material, Li. m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where m ranges from 0.2 to 1.1, and m+x1 ranges from 0.5 to 1.2; The high-lithium manganese-based material is mixed with the positive electrode active material to obtain the composite positive electrode material.

[0014] Preferably, the method for preparing the lithium-rich manganese-based material includes one or more of the following: ion exchange method, coprecipitation method, sol-gel method, solid phase method, hydrothermal method, spray drying method, or combustion method.

[0015] Preferably, the lithium replenishment of the lithium-rich manganese-based material specifically includes: Under an inert atmosphere, weigh out 0.01–0.1 mol / L of lithium replenishment promoter and dissolve it in a solvent. After stirring and dissolving, a clear solution is formed. Based on the amount of lithium-rich manganese-based material to be lithium-replenished and the target lithium replenishment amount m, metallic lithium is added to the clarified solution and stirred continuously to allow the metallic lithium to react with the lithium replenishment promoter and form a lithium-containing complex, thereby obtaining a lithium-replenishing solution; wherein, the amount of metallic lithium is not less than the theoretical stoichiometry required to replenish the lithium-rich manganese-based material to the target lithium replenishment amount m. The lithium-rich manganese-based material to be replenished with lithium is added to the lithium replenishment solution, and the reaction is stirred under an inert atmosphere. After the reaction is completed, the solid product is separated, washed and dried to obtain the high-lithium manganese-based material.

[0016] Preferably, the lithium replenishment promoter includes one or more of 9-fluorenone, pyrene, and biphenyl; The lithium replenishment promoter includes: a single lithium replenishment promoter, or a composite lithium replenishment promoter; The lithium complex formed by the single lithium supplementation promoter has a moderate HOMO energy level; the moderate HOMO energy level is -3.5 eV to -2.5 eV, preferably -3.2 eV to -3.0 eV; The composite lithium replenishment promoter includes at least two lithium replenishment promoters, namely a strong lithium replenishment promoter and a weak lithium replenishment promoter; the lithium complex formed by the strong lithium replenishment promoter and lithium has a relatively high HOMO energy level, -3.0 eV ≤ E HOMO ≤-2.2eV; the lithium complex formed by the weak lithium-compensating promoter and lithium has a relatively low HOMO energy level, -3.7eV≤E HOMO <-3.0eV; In the composite lithium supplementation accelerator, the molar ratio of the strong lithium supplementation accelerator to the weak lithium supplementation accelerator is 1:1-20.

[0017] Thirdly, embodiments of the present invention provide an electrode sheet comprising the composite cathode material described in the first aspect above, or the composite cathode material obtained by the preparation method described in the second aspect above.

[0018] Fourthly, embodiments of the present invention provide a lithium battery comprising the composite cathode material described in the first aspect above, or the composite cathode material obtained by the preparation method described in the second aspect above, or the electrode sheet described in the third aspect above; Preferably, the lithium battery includes one or more of the following: liquid lithium-ion battery, liquid metal lithium battery, hybrid solid-liquid lithium-ion battery, hybrid solid-liquid metal lithium battery, in-situ solidified lithium battery, solid lithium-ion battery, or solid metal lithium battery.

[0019] The composite cathode material containing high-lithium manganese-based materials provided in this invention can overcome the defects of sacrificial cathode lithium replenishment agents and form a complementary advantage between different cathode material systems. Specifically, in addition to the main electrochemical active material, the composite cathode material of this invention also contains 10-30 wt% high-lithium manganese-based materials, thereby pioneering the design of an integrated "lithium replenishment-lithium storage" composite cathode system.

[0020] The high-lithium manganese-based material of the present invention is a material with ultra-high lithium content. Each mole of the high-lithium manganese-based material contains 1.5-2.2 mol of lithium, which is far higher than that of the lithium-rich manganese-based cathode material. It can also be obtained by supplementing lithium to the lithium-rich manganese-based host material.

[0021] During the first charge of the full battery, the high-lithium manganese-based material is able to release at least part of the lithium... mThe additional lithium introduced compensates for the loss of active lithium caused by the formation of a solid electrolyte interface film at the negative electrode and other irreversible reactions in the battery system. This increases the total amount of active lithium that can still participate in subsequent cycles after the first charge-discharge cycle, improving the battery's first-cycle charge capacity and post-formation cycle capacity. Simultaneously, after releasing at least part of the additionally introduced lithium, the high-lithium manganese-based material transforms into a still electrochemically active lithium-rich manganese-based material, rather than forming an inert product that does not participate in subsequent electrochemical reactions. The lithium-rich manganese-based material can continue to participate in reversible lithium insertion and delithiation reactions as a positive electrode active material during subsequent charge-discharge cycles, forming a synergistic positive electrode system with the main positive electrode active material in the composite positive electrode material. This fully utilizes the high specific capacity characteristics of the lithium-rich manganese-based material and avoids the problem of traditional sacrificial lithium replenishers forming inactive products after lithium release and remaining as "dead mass" in the positive electrode for a long time.

[0022] When the high-lithium manganese-based material has a single-crystal structure of O2 phase and / or O3 phase with a median particle size D50 of 1–5 μm and the median particle size D50 of the main positive electrode active material is 8–20 μm, the two can also form a particle size distribution of different sizes. The smaller-sized high-lithium manganese-based material can fill the spaces between the larger-sized main positive electrode active material particles, thereby increasing the packing density and electrode compaction density of the composite positive electrode material, and reducing the direct contact area between the high-lithium manganese-based material and the electrolyte or electrolyte solution. This is beneficial for suppressing interfacial side reactions and improving the cycle stability and safety performance of the composite positive electrode material.

[0023] This invention overcomes the limitations of simple physical blending of existing composite cathode materials and the defect of inactive products formed after lithium release by existing sacrificial lithium replenishing agents. By systematically combining high-lithium manganese-based materials with embedded lithium replenishing functions with cathode active materials, the high-lithium manganese-based materials play a lithium replenishing role in the first charging stage and continue to play a lithium storage activity in the subsequent cycle stage, thereby increasing the total amount of cyclic lithium ions in the battery system. It also forms a synergistic effect in terms of lithium replenishing performance, reversible capacity, particle size distribution, cycle stability and safety performance, thereby improving the specific capacity, energy density, cycle performance and safety performance of the battery system, especially the full battery system. Attached Figure Description

[0024] Figure 1 This is a scanning electron microscope (SEM) image of the high-lithium manganese-based material in Example 2 of the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the cross-section of the composite electrode in Embodiment 2 of the present invention; Figure 3 The image shows the XRD patterns of the O2 phase lithium-rich manganese-based material obtained in step 1 and the O2 phase high-lithium manganese-based material obtained in step 2 of Embodiment 2 of the present invention. Figure 4The first three charge-discharge curves of the high-lithium manganese-based material obtained in Example 2 of this invention are shown below. Figure 5 The first three charge-discharge curves of the half-cell assembled from the composite cathode material-2 obtained in Example 2 of this invention; Figure 6 The first two charge-discharge curves of the full battery assembled from the composite cathode material-2 obtained in Example 2 of this invention; Figure 7 The ARC temperature-time curves of the composite cathode materials of Example 2 and Comparative Examples 1 and 3 of this invention are shown below. Figure 8 The ARC temperature rate-temperature curves of the composite cathode materials of Embodiment 2 and Comparative Examples 1 and 3 of this invention are shown. Figure 9 The image shows the XRD pattern of the O3 phase high-lithium manganese-based material obtained in Example 8 of this invention. Figure 10 The cycle performance curves of the full cells of Example 2 and Comparative Examples 2-4 of this invention are shown. Figure 11 This is the charge-discharge curve of the full battery in the first two cycles of Comparative Example 1 of this invention. Detailed Implementation

[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0026] This invention provides a composite cathode material containing high-lithium manganese-based materials, an electrode sheet, a preparation method, and an application.

[0027] The composite cathode material containing high-lithium manganese-based material proposed in this invention includes: high-lithium manganese-based material and cathode active material.

[0028] The chemical structural formula of the high-lithium manganese-based material is Li m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; of which, Li m The additional lithium intercalation introduced into the lithium-rich manganese-based host material (i.e., LRM cathode material) Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2 occupies tetrahedral sites in the crystal lattice of lithium-rich manganese-based host materials.

[0029] In the above chemical formula, m ranges from 0.2 to 1.1, preferably from 0.4 to 0.8, and can be any value within the above range, including 0.4, 0.5, 0.6, 0.7, and 0.8; x1 ranges from 0.1 to 0.3, preferably from 0.2 to 0.3, and can be any value within the above range, including 0.2, 0.25, and 0.3; m+x1 ranges from 0.5 to 1.2, preferably from 0.6 to 1.1; y1 ranges from 0.01 to 0.2, preferably from 0.02 to 0.15; z1 ranges from 0.03 to 0.2, preferably from 0.03 to 0.15.

[0030] The high-lithium manganese-based material of this invention is a material with ultra-high lithium content. The molar amount of lithium ions per mole of the high-lithium manganese-based material is 1.5-2.2, which can be any value within the above range, including 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.12, 2.15, 2.16, 2.18, and 2.2, preferably 1.6-2.1. Its lithium ion content far exceeds that of existing lithium-rich manganese-based materials. By controlling the lithium ion content per mole of the high-lithium manganese-based material, especially the content of additional lithium ions occupying tetrahedral sites (m value), a high-lithium manganese-based material with optimal performance can be obtained.

[0031] The lithium in LRM cathode materials includes lithium located in the lithium layer and excess lithium located in the transition metal layer; among them, lithium represented by Li1 in the chemical formula mainly occupies the octahedral sites in the layered lithium layer, and Li in the chemical formula x1 The excess lithium primarily occupies octahedral sites in the transition metal layer, corresponding to Li₂MnO₃-type structural units. During the initial charging process, the lithium-rich manganese-based material is activated at higher voltages, with some lithium being converted into lithium. x1 This indicates that excess lithium is extracted from the material lattice, accompanied by lattice oxygen redox reactions and material structural evolution. In a full-cell system, at least a portion of the extracted lithium ions can be used to compensate for the loss of active lithium caused by the formation of a solid electrolyte interface film on the negative electrode side and other irreversible reactions. Due to the potential for lattice oxygen loss, transition metal migration, and local structural rearrangement during the first charge, some of the extracted lithium ions are usually difficult to completely reintegrate into their original lattice sites during subsequent discharges, making it difficult for lithium-rich manganese-based materials to fully recover to their structural state before the first charge.

[0032] This application addresses the aforementioned problems with LRM cathode materials. This application utilizes lithium-rich manganese-based materials, specifically Li... 1+ x1 Ni y1 Co z1 Mn 1-x1-y1-z1Based on O2, further introduce Li m This refers to the further introduction and embedding of lithium into the crystal lattice of lithium-rich manganese-based materials, forming high-lithium manganese-based materials, such as Li. m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2. During the initial charging process, the high-lithium manganese-based material is able to release at least partially Li2O3. m The additional lithium introduced compensates for the loss of active lithium caused by irreversible reactions on the negative electrode side and in the battery system, thereby increasing the amount of active lithium that can still participate in subsequent cycles after the first charge-discharge cycle. Simultaneously, the high-lithium manganese-based material, after releasing at least some of the additionally introduced lithium, transforms into a still electrochemically active lithium-rich manganese-based material (LRM), and can continue to participate in reversible electrochemical reactions as a positive electrode active material during subsequent charge-discharge cycles. This avoids the problem of traditional sacrificial lithium replenishment agents releasing lithium and forming inactive products that occupy the positive electrode space for a long time.

[0033] The high-lithium manganese-based material proposed in this invention has an O2 phase and / or O3 phase single crystal structure, more preferably an O2 phase single crystal structure. The median particle size D50 is 1–5 μm, and can be any value within this range, such as 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.

[0034] Due to their micron-sized particle size, high-lithium manganese-based materials can generate micron-sized O2-phase single-crystal lithium-rich manganese-based materials during electrochemical reaction cycling. This not only exhibits excellent intrinsic rate performance but also achieves optimal particle size distribution with other positive electrode active materials, thereby improving electrode compaction density. Furthermore, compared to the O3-phase structure, O2-phase single-crystal lithium-rich manganese-based materials offer advantages such as lower voltage drop, better cycle stability, more stable structure, and better lithium-ion diffusion performance. The term "pure phase" refers to the absence of characteristic diffraction peaks of other crystalline phases detected in the XRD pattern.

[0035] The high-lithium manganese-based material accounts for 10-30 wt% of the composite cathode material; it can be any value within the above range, including but not limited to 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, and 30 wt%, but is not limited to these. Preferably, it is 15-25 wt%. By limiting the above mass ratio, the lithium replenishment effect can be fully utilized without affecting the dominant role of the electrochemical performance of the main component of the cathode active material, thus forming the best lithium replenishment and compounding effect.

[0036] In addition to high-lithium manganese-based materials, composite cathode materials also include cathode active materials. The median particle size D50 of the cathode active material is 8–20 μm, and can be any value within this range, such as 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, and 20μm. Cathode active materials include: LiCoO2 (LCO) and LiNi. a Mn 2-a O4 or ternary material LiNi 1-x-y Co x M y One or more of O2, etc.; preferably LiCoO2 and / or ternary materials, more preferably high-nickel ternary materials. Among them, LiNi a Mn 2-a In O4, 0 ≤ a ≤ 0.5; LiNi 1-x-y Co x M y In O2, M is either Mn or Al, 0 < x < 0.5, 0 < y < 0.5, and x + y ≤ 0.5.

[0037] The compaction densities of traditional lithium cobalt oxide and ternary cathode materials are approximately 3.4 g / cm³. 3 and 3.1 g / cm 3 Lower compaction density limits further improvement in the volumetric energy density of the battery cell. The composite cathode material of this invention employs a micron-sized particle gradation design, with the cathode active material having a larger median particle size and the high-lithium manganese-based material having a smaller median particle size. The smaller-sized high-lithium manganese-based material can fill the gaps between the larger-sized cathode active material particles, thereby increasing the particle packing density and electrode compaction density of the composite cathode material, and contributing to improved volumetric energy density of the battery cell.

[0038] Furthermore, this invention employs a high-lithium manganese-based material with an O2-phase single-crystal structure to be composited with other positive electrode active materials, utilizing the particle size difference between the two to form a particle size distribution. In particular, when the high-lithium manganese-based material with an O2-phase single-crystal structure is composited with lithium cobalt oxide, the smaller-sized high-lithium manganese-based material particles can fill the spaces between the larger-sized lithium cobalt oxide particles, thereby increasing the particle packing density and electrode compaction density of the composite positive electrode material. This helps to address the problem of limited volumetric energy density in existing lithium-rich manganese-based positive electrode materials due to low electrode compaction density. Simultaneously, the O2-phase single-crystal high-lithium manganese-based material exhibits good structural stability and can play a lithium replenishment role during the initial charging process and continue to participate in the reaction as an electrochemical active material during subsequent cycles. This allows the composite positive electrode material to possess both high discharge specific capacity and good cycle stability, thereby improving the energy density and cycle performance of the battery cell.

[0039] Specifically, when lithium cobalt oxide is used as the main positive electrode active material, the electrode compaction density of the composite positive electrode material can reach 3.8 g / cm³. 3 The above indicates that when ternary materials are used as the main positive electrode active material, the compaction density of the composite positive electrode material can reach 3.4 g / cm³. 3 Therefore, when high-lithium manganese-based materials are combined with positive electrode active materials such as lithium cobalt oxide and ternary materials, a better particle size distribution effect can be formed, thus taking into account lithium replenishment function, reversible capacity and high electrode compaction density.

[0040] In this invention, the median particle size D50 of the high-lithium manganese-based material is 1–5 μm, and the median particle size D50 of the main positive electrode active material is 8–20 μm, forming a particle size distribution of different sizes. Specifically, taking high-voltage lithium cobalt oxide as the positive electrode active material as an example, larger-sized lithium cobalt oxide particles constitute the main particles of the composite positive electrode material, while smaller-sized high-lithium manganese-based material particles are distributed between the lithium cobalt oxide particles and fill at least part of the interparticle gaps. Through the above-mentioned size matching design of large-sized lithium cobalt oxide particles and small-sized high-lithium manganese-based material particles, on the one hand, the particle packing density and electrode compaction density of the composite positive electrode material can be improved; on the other hand, the direct contact area between the high-lithium manganese-based material and the electrolyte or electrolyte solution can be reduced, which is beneficial to suppressing interfacial side reactions and improving the cycle stability and safety performance of the composite positive electrode material. In addition, the dispersion of smaller-sized high-lithium manganese-based material between larger-sized lithium cobalt oxide particles is beneficial to reducing direct contact and local agglomeration between high-lithium manganese-based material particles, thereby improving the interfacial stability and cycle performance of the composite positive electrode material.

[0041] The high-lithium manganese-based cathode material of the present invention, combined with the above-mentioned cathode active material, can achieve a synergistic improvement in safety and energy density. Another major reason is that the high-lithium manganese-based cathode material can not only fully play the role of lithium replenishment agent in the battery to effectively compensate for irreversible lithium consumption, but also generate lithium-rich manganese-based cathode material (LRM) after the first cycle. This product, together with the cathode active material, constitutes the active material component of the composite cathode system, thereby effectively improving the cycle performance and energy density of the battery system.

[0042] Furthermore, this invention fully utilizes the intrinsic thermal stability of the LRM material, a product of the first charge-discharge cycle, which is superior to that of the positive electrode active material (e.g., high-nickel ternary materials, high-voltage LCO). Therefore, it can be introduced as a safety component. The framework of the positive electrode active material (e.g., high-nickel ternary materials, high-voltage LCO) provides good thermal conductivity and structural strength. The LRM filled in it not only does not affect the material structure, but also greatly reduces side reactions by reducing the exposed area of ​​the LRM, thus reducing the risk of gas and heat generation. Therefore, the combination of the two can jointly improve the safety performance of the battery from both the dimensions of material thermal stability and interface stability.

[0043] This invention, through the synergistic design of interparticle gap filling and lattice-intercalated lithium compensation, enables the composite cathode system to achieve a significant increase in reversible capacity while maintaining good processing performance and safety, thereby greatly improving the mass and volumetric energy density of the full cell.

[0044] The composite cathode material containing high-lithium manganese-based materials proposed in this invention can effectively compensate for initial lithium loss during the first charge-discharge cycle. Initial lithium loss includes lithium loss due to the formation of the SEI film on the negative electrode and irreversible loss of the lithium-rich manganese-based material itself. This ensures the integrity of the layered structure of the LRM cathode material produced during the first discharge cycle. Furthermore, during the subsequent first few charge-discharge cycles, the additional lithium ions released by the high-lithium manganese-based material continuously compensate for lithium loss, effectively compensating for the lithium loss of the LRM cathode material during charge-discharge cycles. Therefore, this invention overcomes the limitations of simple blending of existing composite cathode materials. While ensuring high compaction density, excellent cycle stability, and safety, it fundamentally increases the total number of cyclic lithium ions in the entire battery, thereby significantly improving the battery's energy density without sacrificing other performance characteristics.

[0045] The present invention correspondingly proposes a method for preparing the above-mentioned composite cathode material containing high-lithium manganese-based materials. The main steps include: Step 1, Prepare or develop lithium-rich manganese-based materials Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where x1 ranges from 0.1 to 0.3, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2.

[0046] Step 2: Lithium supplementation is performed on the lithium-rich manganese-based material to obtain the high-lithium manganese-based material Li. m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1- z1O2; where m ranges from 0.2 to 1.1, and m+x1 ranges from 0.5 to 1.2.

[0047] Step 3: Mix the high-lithium manganese-based material with the positive electrode active material to obtain a composite positive electrode material containing the high-lithium manganese-based material.

[0048] The lithium-rich manganese-based material in step 1 above can be commercially available or prepared using processes such as ion exchange, co-precipitation, sol-gel, solid-phase, hydrothermal, spray drying, or combustion. Examples of these methods are illustrated below.

[0049] The method for preparing lithium-rich manganese-based materials using ion exchange is as follows: Step 1.1: Mix the sodium source, lithium source, nickel source, cobalt source and manganese source in the required stoichiometric ratio, mix evenly, sieve and dry, and calcine at high temperature in a muffle furnace under an inert atmosphere to obtain the P2 phase sodium layered oxide precursor material, and store it in an argon atmosphere.

[0050] Sodium sources include: sodium carbonate, sodium hydroxide, sodium acetate, or sodium chloride, etc.; lithium sources include: lithium nitrate, lithium carbonate, lithium acetate, lithium oxide, or lithium hydroxide, etc.; nickel sources include: nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, or nickel oxide, etc.; cobalt sources include: cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt acetate, or cobalt oxide, etc.; manganese sources include: manganese sulfate, manganese dioxide, manganese tetroxide, manganese carbonate, manganese oxalate, manganese chloride, or manganese acetate, etc., but are not limited to these. The high-temperature calcination temperature can be 800-1000℃; the calcination time can be 8 hours or more, preferably 8-12 hours. The inert atmosphere can be nitrogen or argon.

[0051] Step 1.2: The P2 phase sodium layered oxide precursor material is uniformly mixed with the lithium salt mixture and subjected to low-temperature heat treatment for a certain time to carry out ion exchange. After the ion exchange reaction is completed, the product is thoroughly washed with deionized water and then vacuum dried to obtain the lithium-rich manganese-based material with the target composition of O2 phase single crystal.

[0052] The lithium salt added in this step is for lithium-sodium ion exchange with the P2 phase sodium layered oxide precursor material to obtain a lithium-rich manganese-based material with an O2 phase single crystal structure. The specific choice of lithium salt is not limited, as long as it enables the above process; preferably, it may include a mixture of LiNO3 and LiCl in a mass ratio of 88:12.

[0053] The low-temperature heat treatment temperature for ion exchange can be 260-300℃; the ion exchange time is preferably more than 4 hours, such as 4-6 hours; the vacuum drying temperature is 100-120℃.

[0054] The method for preparing lithium-rich manganese-based materials using the co-precipitation method is as follows: Step 1.1: Prepare a transition metal salt solution, wherein the molar ratio of Ni:Co:Mn in the transition metal salt solution is y1:z1:(1-x1-y1-z1).

[0055] Among them, the total metal ion concentration in transition metal salts is 0.5-3 mol / L; transition metal ions such as Ni, Co, and Mn can be introduced in the form of sulfates, chlorides, nitrates, etc.

[0056] Step 1.2: Coprecipitation reaction: Add a certain amount of deionized water to the reaction equipment and continuously pass in inert gas. Heat the reaction equipment to above 60°C and add a transition metal salt solution, an alkaline solution and a pH adjuster to the reaction equipment simultaneously while stirring. After the coprecipitation reaction is completed, perform solid-liquid separation, wash and dry the solid material to obtain a spherical hydroxide precursor.

[0057] The pH adjuster is added to control the pH of the reaction system under alkaline conditions.

[0058] The coprecipitation reaction lasts for 12-24 hours.

[0059] Step 1.3: Mix the spherical hydroxide precursor and the lithium source into a homogeneous mixture at a preset molar ratio. First, heat the homogeneous mixture to a first temperature at a first heating rate and hold it at that temperature. Then, heat it to a second temperature at a second heating rate and hold it at that temperature. Allow it to cool naturally to room temperature. After ball milling, sieve the mixture to obtain a lithium-rich manganese-based product.

[0060] Preferably, the spherical hydroxide precursor and the lithium source are mixed at a molar ratio of Li / (Ni+Co+Mn)=1.1-1.3 to ensure the generation of the predetermined lithium-rich manganese-based cathode material.

[0061] The lithium source includes one or more of lithium nitrate, lithium carbonate, lithium acetate, lithium oxide, or lithium hydroxide; preferably lithium carbonate.

[0062] The first heating rate is 3-5°C / min, the first temperature is 450-500°C, and the holding time at the first temperature is 4-8h. Pre-firing is carried out at the first temperature to decompose carbonates and form a preliminary layered structure. The second heating rate is 5-8°C / min, the second temperature is 850-900°C, and the holding time at the second temperature is 10-12h. The main sintering is carried out at the second temperature to promote crystallization into a high-purity lithium-rich phase.

[0063] The lithium-rich manganese-based product was obtained by ball milling through a 200-300 mesh sieve.

[0064] The ion exchange method and coprecipitation method have been described in detail above. Sol-gel method, solid-phase method, hydrothermal method, spray drying method, or combustion method can also be used to prepare the lithium-rich manganese-based material. All of the above methods are well-known material synthesis methods to those skilled in the art. The process conditions, such as raw material ratio, solvent type, reaction temperature, reaction time, calcination temperature, and calcination atmosphere, can be conventionally selected and adjusted according to the properties of the raw materials, the composition of the target material, crystal structure, particle size, and morphology requirements. The specific operating steps and process parameters of the above methods can be determined by those skilled in the art according to actual needs, and will not be elaborated upon here.

[0065] In step 2 above, lithium replenishment for lithium-rich manganese-based materials can be achieved using chemical lithium replenishment, and the specific process is as follows: Step 2.1: Under an inert atmosphere, weigh out the lithium replenishment promoter at a concentration of 0.01–0.1 mol / L and dissolve it in the solvent. Stir to dissolve and form a clear solution. The lithium replenishment promoter is an organic substance capable of meeting a suitable HOMO energy level, preferably an aromatic compound, such as one or more of 9-fluorenone, pyrene, and biphenyl. These components can act as electron transport mediators, promoting the release of lithium ions (Li+) from the lithium metal sheet. + For lithium replenishment promoters, a single lithium replenishment promoter can be used, or two or more lithium replenishment promoters can be used in combination as a composite lithium replenishment promoter.

[0066] Step 2.2: Based on the amount of lithium-rich manganese-based material to be replenished and the target amount of lithium replenishment m, add metallic lithium to the clear solution and stir continuously to allow the metallic lithium to react with the lithium replenishment promoter and form a lithium-containing complex, thereby obtaining a lithium replenishment solution.

[0067] The amount of metallic lithium is not less than the theoretical stoichiometry required to replenish lithium to the target amount m of lithium-rich manganese-based material; metallic lithium can be lithium sheets, lithium wires, lithium balls, lithium powder, etc., and there are no restrictions on its properties and morphology.

[0068] Step 2.3: Add the lithium-rich manganese-based material to be supplemented with lithium to the lithium supplementation solution, stir the reaction under an inert atmosphere, and after the reaction is completed, separate, wash and dry the solid product to obtain the high-lithium manganese-based material.

[0069] Lithium replenishment promoters can form lithium complexes with metallic lithium and act as electron transfer mediators between metallic lithium and lithium-rich manganese-based materials. This promotes electron transfer from metallic lithium to lithium-rich manganese-based materials and simultaneously allows lithium ions to embed into the crystal lattice of the lithium-rich manganese-based materials, thereby obtaining high-lithium manganese-based materials. The electron transfer capability, lithium replenishment reaction kinetics, and thermodynamic stability of the lithium complexes formed by lithium replenishment promoters are related to their HOMO energy levels. Therefore, suitable lithium replenishment promoters can be selected based on the HOMO energy levels of the lithium complexes formed by the lithium replenishment promoter and lithium.

[0070] In some embodiments, the concentration of the lithium replenishment promoter in the lithium replenishment solution is 0.01–0.1 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.08 mol / L, or 0.1 mol / L. The concentration of the lithium replenishment promoter can be adjusted according to the amount of lithium-rich manganese-based material added, the target lithium replenishment amount m, the binding ratio of the lithium replenishment promoter to lithium, and the required lithium replenishment reaction rate.

[0071] Different lithium-addition accelerators can have different binding ratios with lithium. For example, one pyrene molecule or one biphenyl molecule can bind to one lithium, and one 9-fluorenone molecule can bind to two lithiums. Therefore, the amount of metallic lithium required to form a lithium complex can be determined based on the type and amount of the lithium-addition accelerator, as well as the binding ratio between the accelerator and lithium. The amount of metallic lithium should not be less than the theoretical stoichiometry required to lithium-rich manganese-based materials to the target lithium-addition amount m, so that the lithium-addition solution contains sufficient lithium for the lithium-addition reaction.

[0072] For example, when using 0.1 mol / L pyrene as a single lithium-addition promoter, since one pyrene molecule can bind to one lithium molecule, the lithium concentration corresponding to the formed lithium complex can be 0.1 mol / L. When using a composite lithium-addition promoter composed of 9-fluorenone, pyrene, and biphenyl, the total amount of lithium complex that can be formed in the lithium-addition solution can be calculated based on the molar ratio of the three lithium-addition promoters and their respective binding ratios with lithium, and the amount of metallic lithium to be added can be determined accordingly.

[0073] When using a single lithium supplementation promoter, the kinetic performance and thermodynamic feasibility of the lithium supplementation reaction need to be comprehensively considered. In some embodiments, the HOMO energy level of the lithium complex formed by the single lithium supplementation promoter and lithium is -3.5 to -2.5 eV, preferably -3.2 to -3.0 eV.

[0074] In the lithium replenishment system of this application, if the HOMO energy level of the lithium complex is too high, the electron transfer rate from the lithium complex to the lithium-rich manganese-based material may be too fast, easily causing the lithium replenishment reaction to concentrate on the surface of the material particles, resulting in excessive local lithium replenishment, increased lattice stress, particle breakage, or damage to the material structure. If the HOMO energy level of the lithium complex is too low, the electron transfer rate may be slow, requiring a longer reaction time of the lithium-rich manganese-based material in the lithium replenishment solution, which may adversely affect the surface structure and interface stability of the material due to prolonged immersion. Therefore, controlling the HOMO energy level of the lithium complex formed by a single lithium replenishment promoter within the above-mentioned range is beneficial to balancing the kinetic performance, thermodynamic feasibility, and structural stability of the lithium-rich manganese-based material.

[0075] For example, the HOMO levels of lithium complexes formed by biphenyl, pyrene, and 9-fluorenone bound to two lithium atoms are approximately -2.72 eV, -2.99 eV, and -3.20 eV, respectively, with corresponding reduction potentials of approximately 0.25 V, 0.82 V, and 1.32 V. In the systems described in this application, the higher the HOMO level of the lithium complex, the lower its reduction potential, and the faster the kinetics of electron transfer to lithium-rich manganese-based materials. Therefore, the lithium complex formed by biphenyl has relatively fast lithium replenishment kinetics, followed by the lithium complex formed by pyrene, while the lithium complex formed by 9-fluorenone bound to two lithium atoms has relatively slow lithium replenishment kinetics.

[0076] On the other hand, lithium supplementation promoters also need to meet the thermodynamic requirements of the lithium supplementation reaction. The lower the HOMO level of the lithium complex formed by the lithium supplementation promoter and lithium, the more stable the lithium complex is generally, and its reduction potential increases accordingly. However, when the reduction potential is too high, the lithium complex may have difficulty transferring electrons to the lithium-rich manganese-based material, making the lithium supplementation reaction thermodynamically difficult to proceed. For example, the HOMO level of the lithium complex formed by 9-fluorenone bound to one lithium is approximately -3.76 eV, with a corresponding reduction potential of approximately 2 V. The equilibrium potential of the lithium-rich manganese-based material is higher than 2 V; therefore, this lithium complex is unlikely to effectively drive the lithium supplementation reaction of the lithium-rich manganese-based material. In contrast, lithium complexes formed by biphenyl, pyrene, and 9-fluorenone bound to two lithiums can meet the thermodynamic requirements of the lithium supplementation reaction in this application.

[0077] When using a single lithium replenishment promoter, the lithium replenishment reaction rate is mainly adjusted by selecting the HOMO energy level of the lithium complex, but the adjustment range may be limited. If the lithium replenishment reaction rate is too slow, the lithium-rich manganese-based material needs to be immersed in the lithium replenishment solution for a long time, which may cause changes in the surface structure of the material; if the lithium replenishment reaction rate is too fast, it may cause uneven lithium replenishment inside the particles, local lattice stress concentration, and particle breakage. Therefore, in some preferred embodiments, a composite lithium replenishment promoter composed of at least two lithium replenishment promoters is used to further regulate the kinetics of the lithium replenishment reaction.

[0078] Composite lithium-addition promoters include strong lithium-addition promoters with relatively fast kinetics and weak lithium-addition promoters with relatively slow kinetics. The lithium complexes formed by strong lithium-addition promoters and lithium have relatively high HOMO energy levels, satisfying -3.0 eV ≤ E. HOMO ≤-2.2 eV; The lithium complex formed by the weakly lithium-complementing promoter and lithium has a relatively low HOMO energy level, satisfying -3.7 eV ≤ E HOMO <-3.0 eV. In the composite lithium supplementation accelerator, the molar ratio of strong lithium supplementation accelerator to weak lithium supplementation accelerator is 1:1 to 20, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:15, 1:18 or 1:20.

[0079] During the lithium supplementation reaction, electrons are transferred from the HOMO energy level of the organolithium complex to the acceptable energy level of the corresponding transition metal element in the lithium-rich manganese-based material. The energy level difference between the HOMO energy level of the organolithium complex and the corresponding energy level in the lithium-rich manganese-based material affects the activation energy of electron transfer, thus influencing the lithium supplementation reaction rate. By combining strong and weak lithium supplementation promoters, the differences in electron transfer capacity and reaction rate between different lithium complexes can be utilized to regulate the lithium supplementation reaction process, allowing it to proceed at a relatively suitable and uniform rate.

[0080] Therefore, composite lithium replenishment promoters can reduce the problem of excessively fast or slow lithium replenishment rates that may occur when using a single lithium replenishment promoter. While ensuring that lithium-rich manganese-based materials have a high degree of lithium replenishment, they can reduce the adverse effects of the lithium replenishment reaction on the particle morphology and crystal structure of the materials.

[0081] The degree of lithium replenishment in lithium-rich manganese-based materials can be adjusted by process conditions such as the type and concentration of the lithium replenishment promoter, the molar ratio between different lithium replenishment promoters, the amount of lithium metal added, the solid-liquid ratio of the lithium-rich manganese-based material to the lithium replenishment solution, the reaction temperature, and the reaction time. By controlling these process conditions, the lithium replenishment degree of lithium-rich manganese-based materials can be adjusted by adjusting the lithium metal added. m The lithium is inserted into the lattice of a lithium-rich manganese-based material to obtain the chemical formula Li. m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2-rich manganese-based materials.

[0082] The target lithium replenishment amount *m* and the amount of high-lithium manganese-based material mixed in the composite cathode material can be determined based on the initial coulombic efficiency of the anode, the irreversible capacity during the first charge-discharge cycle of the anode, and the capacity matching relationship between the positive and negative electrodes of the full cell. These can be adjusted in conjunction with the interfacial stability, cycle performance, and actual lithium replenishment effect of the composite cathode material. Specifically, the amount of active lithium to be compensated during the first charge-discharge cycle of the full cell can be calculated based on the irreversible capacity during the first charge-discharge cycle of the anode, and the target lithium replenishment amount *m* of the lithium-rich manganese-based material and the amount of high-lithium manganese-based material mixed in the composite cathode material can be determined accordingly.

[0083] The following section uses a composite cathode material composed of lithium cobalt oxide and high-lithium manganese-based materials as an example to explain how to determine the target lithium replenishment amount m and the amount of high-lithium manganese-based materials mixed in.

[0084] The lithium cobalt oxide cathode material exhibits an initial charge specific capacity of 208 mAh / g, an initial discharge specific capacity of 205 mAh / g, and a median particle size of 8 μm; the lithium-rich manganese-based material demonstrates an initial charge specific capacity of 290 mAh / g, an initial discharge specific capacity of 270 mAh / g, and a median particle size of 2 μm; the high-lithium manganese-based material Li... 1.82 Ni 0.02 Co 0.03 Mn 0.73 The initial charge specific capacity of O2 is 460 mAh / g, and the initial discharge specific capacity is 270 mAh / g; the initial discharge specific capacity of silicon-carbon anode material is 870 mAh / g, and the initial charge specific capacity is 740 mAh / g.

[0085] When the composite cathode material includes 80 wt% lithium cobalt oxide and 20 wt% lithium-rich manganese-based material, the initial discharge specific capacity of the composite cathode material is approximately: 205×0.8+270×0.2=218 mAh / g.

[0086] When the ratio of the positive to negative capacity of the full battery is 1.08, and the initial charge specific capacity of the silicon-carbon negative electrode material is 740 mAh / g, the mass of silicon-carbon negative electrode material corresponding to each 1 g of composite positive electrode material is approximately: 218 × 1.08 ÷ 740 = 0.3182 g.

[0087] The initial irreversible specific capacity of the silicon-carbon anode material is: 870-740=130 mAh / g.

[0088] Therefore, the irreversible capacity corresponding to the active lithium consumed by 0.3182 g of silicon-carbon anode material during the first charge-discharge process is approximately: 0.3182 × 130 = 41.366 mAh.

[0089] When the composite cathode material includes 80 wt% lithium cobalt oxide and 20 wt% ordinary lithium-rich manganese-based material, the initial charging capacity of each 1 g of composite cathode material is approximately: 208×0.8+290×0.2=224.4 mAh.

[0090] After deducting the initial irreversible capacity of the negative electrode, the remaining active lithium in the battery system corresponds to a capacity of approximately 224.4 - 41.366 = 183.034 mAh.

[0091] When using 20 wt% high lithium manganese-based material Li 1.82 Ni 0.02 Co 0.03 Mn 0.73 When O2 replaces ordinary lithium-rich manganese-based materials, the initial charging capacity of each 1 g of composite cathode material is approximately: 208×0.8+460×0.2=258.4 mAh.

[0092] After deducting the initial irreversible capacity of the negative electrode, the remaining active lithium in the battery system corresponds to a capacity of approximately 258.4 - 41.366 = 217.034 mAh.

[0093] Therefore, compared with the composite cathode using ordinary lithium-rich manganese-based materials, the capacity corresponding to the remaining active lithium in the battery system is increased by approximately 217.034-183.034=34 mAh after using high-lithium manganese-based materials, which is approximately 34÷183.034×100%=18.6%.

[0094] The above calculations are primarily used to illustrate the methods for determining the target lithium replenishment amount *m* and the blending amount of high-lithium manganese-based materials, without considering side reactions at the cathode side interface or other irreversible lithium losses in the battery system. In practical applications, the target lithium replenishment amount *m* and the blending amount of high-lithium manganese-based materials can be further adjusted based on the types of cathode and anode active materials, the initial coulombic efficiency, the capacity matching relationship between the cathode and anode, and the full-cell test results.

[0095] In the preparation process of this invention, high-lithium manganese-based materials are obtained by additionally supplementing lithium to lithium-rich manganese-based cathode materials. By employing an innovative lithium supplementation process, the kinetics of the lithium supplementation reaction can be effectively controlled, enabling rapid diffusion of lithium ions into the bulk structure of the lithium-rich manganese-based material in a liquid phase system without disrupting its original structure. This achieves effective and sufficient lithium supplementation, transforming the material into an electrochemically active lithium-rich manganese-based material. When two or more lithium supplementation promoters are used in combination, such as pyrene and 9-fluorenone, the precise and controllable kinetics of lithium supplementation in the lithium-rich manganese-based material can be effectively achieved.

[0096] In summary, this invention employs a high-lithium manganese-based material compounded with other positive electrode active materials. During the first charge-discharge cycle, it effectively compensates for the irreversible lithium loss of the entire battery, thus overcoming the poor cycle performance caused by significant lithium consumption on the negative electrode side. Besides acting as a lithium replenisher, the high-lithium manganese-based positive electrode material of this invention can directly transform into a high-capacity lithium-rich manganese-based active material product after the first charge cycle. This product forms a synergistic system with other active materials in the composite positive electrode, leveraging the advantages of each material: the intrinsic thermal stability of the lithium-rich manganese-based material and the cycle stability of the other active materials. Furthermore, it utilizes the compounding advantages between the positive electrode materials, with the lithium-rich manganese-based material filling the framework structure of other positive electrode active materials, thereby significantly reducing the contact area with the electrolyte or solid electrolyte. Through the synergistic design of interparticle filling and lithium replenishment by the high-lithium manganese-based material, this invention significantly improves the battery's safety performance and specific capacity.

[0097] This invention, through the aforementioned lithium replenishment process, maintains the main crystal structure of lithium-rich manganese-based materials while refining the lithium content of the materials. mThe lithium is embedded in its lattice to obtain a high-lithium manganese-based material; the high-lithium manganese-based material releases at least part of the lithium during the first charge. m After being converted to lithium, it can be transformed into a lithium-rich manganese-based cathode material that still has electrochemical activity and continues to participate in reversible electrochemical reactions in subsequent charge-discharge cycles.

[0098] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0099] The reagents and materials used in the following examples and comparative examples, including electrolytes, electrolyte additives, and lithium metal anodes, are all commercially available conventional reagent products and can also be prepared using conventional methods. Where specific experimental steps or conditions are not specified in the examples, they should be performed according to conventional experimental procedures or conditions in the art.

[0100] For example, the median particle size D50 of the material in this invention can be the median value sorted by volume, mass, or quantity. In this embodiment of the invention, the median particle size sorted by quantity represents the particle size that accounts for 50% of the total quantity distribution. Particle size D50 is a well-known concept in the art. The particle size of the material provided in this embodiment of the invention can be determined using instruments and conventional methods known in the art. Specifically, in this embodiment, the particle size is determined using a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0101] Example 1 This embodiment uses Li 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-1 was prepared by mixing O2 and LiCoO2 at a mass ratio of 20:80. Among them, Li... 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0102] Step 1: Preparation of lithium-rich cathode material Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0103] First, Na₂CO₃, Li₂CO₃, NiO, Co₃O₄, and MnO₂ are mixed in stoichiometric proportions to obtain the sodium layered oxide precursor Na₁Li with the corresponding target chemical composition. 0.22 Ni 0.02 Co 0.03 Mn 0.73 O2 is mixed evenly, sieved and dried, pressed into sheets, and then calcined in a muffle furnace at 800°C for 10 hours under an inert atmosphere to obtain P2 phase material, which is then stored in an argon atmosphere.

[0104] Then, the P2 phase material was uniformly mixed with a mixture of LiNO3 and LiCl, wherein the mass ratio of LiNO3 to LiCl was 88:12 and the molar ratio of P2 phase material to Li in the mixture was 1:10. The mixture was then heat-treated at 280℃ for 4 hours for ion exchange. After the ion exchange reaction, the product was thoroughly washed with deionized water and then vacuum-dried at 120℃ for 6 hours to finally obtain a lithium-rich manganese-based material with the target composition of O2 phase single crystals.

[0105] Step 2: Preparation of high-lithium manganese-based material Li 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0106] Under an argon atmosphere, prepare 10 ml of a combined lithium supplementation agent solution with a total lithium supplementation agent concentration of 0.1 mol / L. Weigh the corresponding mass of organic lithium supplementation agent according to the molar ratio of pyrene:9-fluorenone = 1:9 and dissolve it in 10 ml of tetrahydrofuran. Stir until completely dissolved to form a clear solution. Weigh 0.0132 g of metallic lithium into the above solution and continue stirring until the metallic lithium is completely dissolved to obtain the lithium supplementation solution.

[0107] According to the lithium replenishment target, 0.2084 g of Li was added to the above solution. 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 was added and stirred for 30 minutes under an argon atmosphere. After the reaction was completed, the solid product was separated, washed, and dried to obtain the high-lithium manganese-based material Li. 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0108] Step 3: Li 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73The composite of O2 and LiCoO2.

[0109] Weigh Li according to a mass ratio of 20:80 0.4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material-1.

[0110] Electrochemical performance characterization: 1) Electrode preparation: Composite positive electrode material-1, conductive agent Super-P, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, with N-methylpyrrolidone (NMP) as solvent, and stirred in a planetary ball mill for 1 hour to prepare a uniform electrode slurry. The electrode slurry was uniformly coated onto an aluminum foil current collector and dried in a vacuum drying oven at 80℃ for 12 hours. Subsequently, it was pressed into sheets using a 20MPa roller press, with a compaction density of 3.9 g / cm³. 3 The electrode was cut into circular electrode sheets with a diameter of 12 mm, and the active material loading was 10 ± 0.5 mg / cm³. 2 .

[0111] 2) Battery assembly: In an argon-protected glove box (water and oxygen content ≤1ppm), assemble a CR2032 coin cell with an electrode sheet as the positive electrode, a lithium metal sheet as the negative electrode, Celgard 2400 as the separator, and an electrolyte of 1mol / L LiPF6 / ethylene carbonate (EC) + dimethyl carbonate (DMC) + diethyl carbonate (EMC) (EC, DMC, EMC volume ratio 1:1:1) and let it stand for 24 hours.

[0112] 3) Performance testing: Electrochemical performance was tested using a battery testing system. Test conditions: charge and discharge voltage range 3.0-4.6V, formation was carried out at a charge and discharge rate of 0.1C for the first two weeks, and from the third week onwards, 100 charge and discharge cycles were carried out at a rate of 0.5C (1C=200mAh / g). The test temperature was 25℃.

[0113] Test Results and Analysis: The battery's initial charge capacity at 0.1C was 246 mAh / g, and its initial discharge capacity was 215 mAh / g, with a charge-discharge capacity difference of 31 mAh / g. At 0.5C, the initial discharge capacity was 207 mAh / g, and after 100 cycles at 0.5C, the discharge capacity was 182 mAh / g, exhibiting a capacity retention rate of 88% and excellent cycle stability. For the lithium-ion half-cell with the negative electrode, the 31 mAh / g difference between the initial charge and discharge capacity at 0.1C indicates that it can replenish the corresponding 31 mAh / g of lithium loss in the first cycle, demonstrating a significant advantage when applied to full-cell batteries. Electrochemical performance tests of the half-cell showed that the electrode maintained a stable voltage plateau during charge and discharge, with no significant voltage decay.

[0114] Example 2 This embodiment uses Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-2 was prepared by mixing O2 and LiCoO2 in a mass ratio of 20:80. Among them, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0115] Step 1: Same as in Example 1.

[0116] Step 2: Preparation of high-lithium manganese-based material Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0117] Under an argon atmosphere, prepare 10 ml of a combined lithium supplementation agent solution with a total lithium supplementation agent concentration of 0.1 mol / L. Weigh the corresponding mass of organic lithium supplementation agent according to the molar ratio of pyrene:9-fluorenone = 1:4 and dissolve it in 10 ml of tetrahydrofuran. Stir until completely dissolved to form a clear solution. Weigh 0.0125 g of metallic lithium into the above solution and continue stirring until the metallic lithium is completely dissolved to obtain the lithium supplementation solution.

[0118] According to the lithium replenishment target, 0.1390 ​​g of Li was added to the above solution. 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 was added and stirred for 30 minutes under an argon atmosphere. After the reaction was completed, the solid product was separated, washed, and dried to obtain the high-lithium manganese-based material Li. 0.6 Li1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0119] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 20:80 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material-2.

[0120] Performance characterization: Morphological characterization: Scanning electron microscopy (SEM) of high-lithium manganese-based materials, such as... Figure 1 As shown, the high-lithium manganese-based material consists of micron-sized particles with good particle condition, a uniform and smooth surface without cracks, and a particle size D50 of 2 μm as tested. Figure 2 The image shows an SEM image of the initial electrode cross-section obtained from the composite cathode material formed by high-lithium manganese-based material and lithium cobalt oxide. As can be seen from the image, a particle size distribution of large and small particles is formed between the two materials, and the electrode obtained by rolling has a very high density.

[0121] Structural characterization: such as Figure 3 As shown, both the lithium-rich manganese-based material obtained in step 1 of Example 2 and the high-lithium manganese-based material obtained in step 2 exhibit characteristic peaks of the O2 phase structure. Powder X-ray diffraction (XRD) characterization revealed that the oxygen layers in the O2-phase lithium-rich manganese-based material are arranged in an ABAC stacking sequence, exhibiting typical characteristics of an O2-type layered structure. The XRD pattern shows a (002) characteristic diffraction peak near 2θ (approximately 18°), related to the layered stacking structure of the O2 phase. Combined with the crystallographic characteristics of this O2-type layered oxide, it is thus confirmed that the lithium-rich manganese-based material possesses a layered O2 phase structure with space group P63mc.

[0122] Furthermore, after lithium replenishment treatment, the XRD pattern of the lithium-rich manganese-based material showed identifiable changes compared to the unreplenished sample, mainly manifested as a shift of the characteristic diffraction peak of the O2 phase at approximately 18° 2θ to a higher angle. These results indicate that lithium ions are embedded into the layered lattice structure of the lithium-rich manganese-based material during the lithium replenishment process, effectively supplementing the lithium content while maintaining the layered O2 phase structure.

[0123] Electrochemical performance characterization: 1) Electrode preparation and battery assembly: using high-lithium cathode material Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and composite cathode material-2 were used as the positive electrode active materials. Battery electrodes were prepared using the same electrode preparation method as in Example 1. The resulting electrode compaction densities were 3.1 g / cm³. 3 and 3.92g / cm 3 The loading of active material on the electrodes was 10 ± 0.5 mg / cm³. 2 .

[0124] The battery assembly is the same as in Example 1.

[0125] 2) Performance Testing: The test conditions were the same as in Example 1.

[0126] High-lithium manganese-based materials Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 test results are as follows Figure 4 As shown, the charging capacity in the first cycle is 457 mAh / g, and the discharging capacity is 281 mAh / g; the charging capacity in the second cycle is 282 mAh / g, and the discharging capacity is 279 Ah / g; and the charging capacity in the third cycle (0.5C) is 242 mAh / g, and the discharging capacity is 240 mAh / g. This indicates that the material can provide a specific capacity of 176 mAh / g during the first charge and discharge cycle, making it an effective lithium replenishment component. From the second cycle onwards, the difference in the charging and discharging specific capacities of the material is very small, indicating that it can remain stable as a positive electrode active material for a long time. This demonstrates that the high-lithium manganese-based material does not lose its activity even after achieving the lithium replenishment target, but successfully transforms into a high-capacity, recyclable positive electrode material.

[0127] The test results of the composite cathode material-2 are as follows: Figure 5 As shown: the battery's charging capacity at 0.1C is 258 mAh / g, and its initial discharge capacity is 218 mAh / g, with a charge-discharge capacity difference of 40 mAh / g. At 0.5C, the initial discharge capacity is 209 mAh / g in the first week, and after 100 cycles, the discharge capacity is 182 mAh / g, exhibiting a capacity retention of up to 87% and excellent cycle stability. Half-cell testing shows that at 0.1C, it can replenish the corresponding 40 mAh / g of lithium loss in the first week. Electrochemical testing shows that the electrode has a stable voltage plateau during charge and discharge with no significant voltage decay, achieving a balance between high lithium removal capacity and excellent cycle performance.

[0128] 3) Full cell assembly: The negative electrode uses silicon-carbon material, and the positive electrode surface loading of the soft pack is approximately 19 ± 0.5 mg / cm³. 2 The overall np ratio of the battery is 1.08. The full battery charge / discharge voltage range is 3.0-4.5V. The formation charge / discharge rate is 0.1C for the first two weeks, and 0.5C (1C=200mAh / g) from the third week onwards. The charge / discharge cycle count is 300 cycles, and the test temperature is 25℃.

[0129] Cyclic performance test analysis of the full battery: such as Figure 6 As shown, the initial charge capacity of the pouch battery at 0.1C is 255mAh / g, the initial discharge capacity is 213mAh / g, and the difference between charge and discharge capacity is 42mAh / g; Figure 10 As shown, the initial discharge capacity at 0.5C is 202 mAh / g, and the discharge capacity after 300 cycles is 167.7 mAh / g. The full-cell test shows that the composite cathode material can effectively replenish lithium consumption due to the lithium replenishment effect of the high-lithium manganese-based material. At 0.5C, not only is the specific capacity fully utilized, but the cycle stability is also excellent. Through reasonable compound design, the additional delithiation of the cathode can effectively offset the lithium consumption of the anode.

[0130] ARC characterization: The thermal stability of the samples was tested using accelerating rate calorimetry (ARC). The ARC equipment was from THT Corporation, model EV+ARC. The test parameters were set as follows: the positive electrode sheet formed from the composite positive electrode material-2 was placed in the equipment; the initial temperature was set to 50℃, the final temperature to 305℃, and the temperature was gradually increased in 5℃ increments, with a holding time of 30 min at each temperature; the exothermic tracking condition was set to a temperature rise rate greater than 0.02℃ / min. When this condition was met, the system automatically entered adiabatic tracking mode to record the thermodynamic data during the reaction process. The test results are as follows: Figure 7 and Figure 8 As shown. Figure 7 As shown, in Example 2, the thermal runaway occurred later, with the self-exothermic initiation temperature T1 being approximately 91°C, while the highest thermal runaway temperature T3 was approximately 480°C; Figure 8 As shown, in Example 2, the T2 corresponding to the battery self-heating reaching 60℃ / min is 175℃.

[0131] Example 3 This embodiment uses Li 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-3 was prepared by mixing O2 and LiCoO2 at a mass ratio of 20:80. Among them, Li...0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 5 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0132] Step 1: Same as in Example 1.

[0133] Step 2: Preparation of high-lithium manganese-based material Li 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0134] Under an argon atmosphere, prepare 10 ml of a combined lithium supplementation agent solution with a total lithium supplementation agent concentration of 0.1 mol / L. Weigh out the corresponding mass of organic lithium supplementation agent according to the molar ratio of pyrene:9-fluorenone = 1:1 and dissolve it in 10 ml of tetrahydrofuran. Stir until completely dissolved to form a clear solution. Weigh 0.0105 g of metallic lithium into the above solution and continue stirring until the metallic lithium is completely dissolved to obtain the lithium supplementation solution.

[0135] According to the lithium replenishment target, 0.1042 g of Li was added to the above solution. 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 was added and stirred for 30 minutes under an argon atmosphere. After the reaction was completed, the solid product was separated, washed, and dried to obtain the high-lithium manganese-based material Li. 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2.

[0136] Step 3: Li 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 20:80 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material-3.

[0137] Electrochemical performance characterization: 1) Electrode preparation and battery assembly: Composite cathode material-3 was used as the cathode active material. Battery electrodes were prepared and batteries were assembled according to the same electrode preparation method as in Example 1.

[0138] 2) Performance Testing: The test conditions were the same as in Example 1.

[0139] Test Results and Analysis: The battery's initial charge capacity at 0.1C was 268 mAh / g, and its initial discharge capacity was 210 mAh / g, with a charge / discharge capacity difference of 58 mAh / g. At 0.5C, the initial discharge capacity was 211 mAh / g, and after 100 cycles, the discharge capacity was 161 mAh / g. Half-cell testing shows that at 0.1C, it can replenish the corresponding 58 mAh / g of lithium loss in the first week, demonstrating a higher lithium replenishment effect. However, compared to Examples 1 and 2, due to the excess lithium in the lithium-rich manganese-based material Li... 0.8 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 contains a high Li content. Excessive lithium supplementation can cause partial distortion of the internal crystal structure of high-lithium materials, resulting in a decrease in structural stability. This leads to a slight decrease in the reversible capacity and cycle performance of lithium-rich materials, but they still exhibit good electrochemical performance.

[0140] Example 4 This embodiment uses Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-4 was prepared by mixing O2 and LiCoO2 at a mass ratio of 15:85. Among them, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 5 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0141] Steps 1 and 2: Same as in Example 2.

[0142] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 15:85. 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73O2 and LiCoO2 are mixed to obtain composite cathode material-4.

[0143] Electrochemical performance characterization: 1) Electrode preparation and battery assembly: Composite cathode material-4 was used as the positive electrode active material. Conductive agent Super-P and binder polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 90:5:5, with N-methylpyrrolidone (NMP) as solvent, and stirred in a planetary ball mill for 2 hours to prepare a uniform electrode slurry. The electrode slurry was uniformly coated onto an aluminum foil current collector and dried in an 80℃ vacuum drying oven for 12 hours. Subsequently, it was pressed into sheets using a 20MPa roller press, achieving a compaction density of 3.87 g / cm³. 3 The electrode was cut into circular electrode sheets with a diameter of 12 mm, and the active material loading was 10 ± 0.5 mg / cm³. 2 .

[0144] The battery assembly is the same as in Example 1.

[0145] Test Results and Analysis: At 0.1C, the battery's initial charge capacity was 246 mAh / g, and its initial discharge capacity was 215 mAh / g, with a charge-discharge capacity difference of 31 mAh / g. At 0.5C, the initial discharge capacity was 206.8 mAh / g, and after 100 cycles, the discharge capacity was 181 mAh / g, with a capacity retention rate of 87.5%, indicating good cycle stability. Half-cell testing showed that at 0.1C, it could replenish the corresponding 31 mAh / g lithium loss in the first week. Compared to Example 2, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The low proportion of O2 and high proportion of LCO result in improved cycle stability of the composite cathode material, with slightly lower additional lithium removal in the first week compared to Example 2.

[0146] Example 5 This embodiment uses Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-5 was prepared by mixing O2 and LiCoO2 in a mass ratio of 25:75. Among them, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 5 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0147] Steps 1 and 2: Same as in Example 2.

[0148] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 25:75. 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material-5.

[0149] Electrochemical performance characterization: The electrode preparation and battery assembly were the same as in Example 4, and the resulting electrode compaction densities were 3.84 g / cm³. 3 .

[0150] Test Results and Analysis: At 0.1C, the battery's initial charge capacity was 271 mAh / g, and its initial discharge capacity was 219 mAh / g, with a charge-discharge capacity difference of 52 mAh / g. At 0.5C, the initial discharge capacity was 211 mAh / g, and after 100 cycles, the discharge capacity was 179 mAh / g, with a capacity retention rate of 84.8%. Half-cell testing showed that at 0.1C, it could replenish the corresponding 52 mAh / g lithium loss in the first cycle. Compared to Examples 2 and 4, the composite cathode material with this gradation ratio can fully utilize Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2's high delithiation rate results in a significant capacity improvement.

[0151] Example 6 This embodiment uses Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material-6 was prepared by mixing O2 and LiCoO2 in a mass ratio of 30:70. Among them, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 5 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0152] Steps 1 and 2: Same as in Example 2.

[0153] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 30:70. 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material-6.

[0154] Electrochemical performance characterization: The electrode preparation and battery assembly were the same as in Example 4, and the resulting electrode compaction densities were 3.80 g / cm³. 3 .

[0155] Test Results and Analysis: The 0.1C battery had an initial charge capacity of 283 mAh / g and an initial discharge capacity of 222 mAh / g, with a charge / discharge capacity difference of 61 mAh / g. The 0.5C battery had an initial discharge capacity of 213.5 mAh / g, and after 100 cycles at 0.5C, the discharge capacity was 180 mAh / g, with a capacity retention rate of 84.3%. Half-cell testing showed that at 0.1C, it could replenish the corresponding 61 mAh / g of lithium loss in the first week. Compared to Example 5, Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The increased lithium content in O2 slightly improved discharge capacity, but reduced cycle stability. This is because the high proportion of high-lithium manganese-based materials, while increasing delithiation and capacity, negatively impacted the overall structural stability of the material, leading to a slight capacity decay during cycling.

[0156] Example 7 This embodiment uses Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiNi 0.8 Co 0.1 Mn 0.1 A composite cathode material-7 was prepared using O2 (NCM811) at a mass ratio of 20:80. Among the components, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; NCM811 particles have a diameter of 10 μm and a purity of ≥99.8%.

[0157] Steps 1 and 2: Same as in Example 2.

[0158] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and NCM811 composite: Weigh Li according to a mass ratio of 20:80 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and NCM811 are mixed to obtain composite cathode material-7.

[0159] Electrochemical performance characterization: 1) Electrode preparation: Composite positive electrode material-7, conductive agent acetylene black (AB), and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, with N-methylpyrrolidone (NMP) as solvent, and stirred in a planetary ball mill for 2 hours to prepare a uniform electrode slurry. The electrode slurry was uniformly coated onto an aluminum foil current collector and dried in an 80℃ vacuum drying oven for 12 hours. Subsequently, it was pressed into sheets using a roller press, with a compaction density of 3.4 g / cm³. 3 The electrode was cut into circular electrode sheets with a diameter of 12 mm, and the active material loading was 10 ± 0.5 mg / cm³. 2 .

[0160] 2) Battery assembly: Same as in Example 2.

[0161] 3) Performance testing: Electrochemical performance was tested using a battery testing system. Test conditions: charge / discharge voltage range 2.5-4.3V, charge / discharge rate 0.5C (1C=200mAh / g, formation 0.1C), 100 charge / discharge cycles, and test temperature 25℃.

[0162] Test Results and Analysis: At 0.1C, the battery's initial charge capacity was 266 mAh / g, and its initial discharge capacity was 225 mAh / g, with a charge-discharge capacity difference of 41 mAh / g. At 0.5C, the initial discharge capacity was 214 mAh / g, and after 100 cycles, the discharge capacity was 187 mAh / g, demonstrating superior cycle performance. However, its ultimate compaction density was lower than that of the lithium cobalt oxide material in Example 2, mainly because the true density and compaction density of the ternary material were lower than those of the LCO material. Half-cell testing showed that at 0.1C, it could replenish the corresponding 41 mAh / g of lithium loss in the first week.

[0163] Example 8 In the preparation process of this invention, a co-precipitation method is used to prepare lithium-rich manganese-based materials with the O3 phase, and after lithium supplementation, high-lithium manganese-based materials Li are obtained. 0.6 Li 1.2 Ni 0.13 Co0.13 Mn 0.54 O2 was used to prepare a composite cathode material-8 by mixing high-lithium manganese-based materials with LiCoO2 at a mass ratio of 20:80.

[0164] Step 1: Preparation of lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2; 1) Preparation of transition metal salt solutions Prepare the solution according to the molar ratio of Ni:Co:Mn = 1:1:4, with a total transition metal ion concentration of 0.5 mol / L. Weigh out 0.125 mol of NiSO4·6H2O, 0.125 mol of CoSO4·7H2O, and 0.500 mol of MnSO4·H2O, dissolve them in deionized water, and bring the volume to 1.5 L. Stir until completely transparent to obtain a transition metal salt solution.

[0165] 2) Coprecipitation reaction First, add 500 mL of deionized water to the reaction apparatus and purge with N2 for protection (to remove oxygen). Then, heat the reaction apparatus to 60°C and control the stirring speed to 400–600 rpm.

[0166] Simultaneously pump the transition metal salt solution obtained in step 1), 2 mol / L NaOH solution, and concentrated ammonia solution into the reaction apparatus; the concentrated ammonia solution is used to control the pH of the solution, maintaining the pH of the solution system at 11.0 ± 0.1. The co-precipitation reaction is carried out continuously for 12-24 hours; the feeding is stopped, and stirring and aging are continued for 4 hours; solid-liquid separation is performed by vacuum filtration, and the product is washed with deionized water until the pH of the filtrate is 7; then washed 1-2 times with anhydrous ethanol; the solid product is placed in a vacuum oven and dried at 60°C for 12 hours to obtain the spherical hydroxide precursor Ni. 0.2 Co 0.2 Mn 0.6 (OH)2.

[0167] 3) Sintering reaction The theoretical amount of Li₂CO₃ to be added was calculated based on the molar ratio Li / (Ni+Co+Mn) = 1.20, and an excess of 5% was added, i.e., Li₂CO₃ was added according to the actual molar ratio Li / (Ni+Co+Mn) = 1.26. The precursor powder and Li₂CO₃ were mixed, wet-milled with ethanol for 4 h, dried, and a homogeneous mixture was obtained.

[0168] 4) Segmented high-temperature sintering Under air atmosphere, the temperature was increased to 450°C at a heating rate of 3°C / min and held for 4 h for the first sintering; then, the temperature was increased to 850–900°C at a heating rate of 5°C / min and held for 10–12 h for the second sintering; the sintered product was ground for 30 min and passed through a 200–300 mesh sieve to obtain the lithium-rich manganese-based product Li. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0169] Step 2: Preparation of high-lithium manganese-based materials 1) Preparation of organic lithium supplementation solution: Weigh 0.1542g of lithium supplementation promoter biphenyl, 0.1802g of 9-fluorenone and 0.2022g of pyrene, dissolve them in 10 ml of anhydrous tetrahydrofuran (THF), stir until completely dissolved to form a clear solution, add 0.01388g of lithium metal flakes to the solution, and continue stirring until the lithium metal is completely dissolved to obtain a 0.1M organic lithium supplementation solution.

[0170] 2) Chemical lithium supplementation reaction: 0.1424g of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The O2 matrix material was added to the above-mentioned organolithium lithium supplementation solution, and the mixture was stirred under an inert atmosphere for 0.5 h. After stirring was stopped and the product settled to the bottom, the lithium supplementation solution was removed to obtain a solid product. The solid product was washed with anhydrous THF, and the washing was repeated 3-4 times until the washing solution was colorless. The obtained solid product was then dried for later use.

[0171] Product Drying and Characterization: The washed solid product was placed in a vacuum drying oven and dried until the mass was constant. The lithium content of the product was determined by ICP-OES, and the crystal structure of the product was detected by XRD. Qualified Li was screened out. 0.6 Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 products.

[0172] Step 3: Li 0.6 Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The combination of O2 and LiCoO2: Composite cathode material-8 was obtained by mixing 20 wt% high-lithium manganese-based material with 80 wt% lithium cobalt oxide, the positive electrode active material.

[0173] Structural characterization: such as Figure 9 As shown, XRD tests indicate that the Li obtained in step 1 via co-precipitation...1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 has an O3 phase structure. The XRD pattern shows characteristic diffraction peaks at approximately 19°, 38°, 43°, and 60° at 2θ, indicating that the high-lithium manganese-based material has an O3 phase structure.

[0174] Electrochemical performance characterization: Same as in Example 4.

[0175] Test Results and Analysis: At 0.1C, the battery charging capacity is 252 mAh / g, the initial discharge capacity is 211 mAh / g, and the difference between charge and discharge capacity is 41 mAh / g. At 0.5C, the initial discharge specific capacity is 198 mAh / g, and after 100 cycles, the discharge capacity is 162 mAh / g, with a capacity retention rate of 82%. Half-cell testing shows that at 0.1C, it can replenish the corresponding 41 mAh / g of lithium loss in the first cycle. Compared with O2-phase high-lithium manganese-based materials, the high-lithium manganese-based materials with O3-phase structures exhibit a lower capacity release at 0.5C. This also indicates that O2-phase high-lithium manganese-based materials have advantages.

[0176] Example 9 This embodiment uses composite cathode material-2.

[0177] Full cell assembly: The positive and negative electrode specifications are the same as in Example 2, and in-situ polymerization is used instead of electrolyte injection. Specific formulation of the precursor solution: 88.7 wt% 1.0 mol / L lithium hexafluorophosphate (LiPF6) carbonate base electrolyte, 8.0 wt% trimethylolpropane ethoxytriacrylate (ETPTA), 3.0 wt% fluoroethylene carbonate (FEC), and 0.3 wt% azobisisobutyronitrile (AIBN) thermal initiator; wherein the base electrolyte solvent is a 1:1 volume ratio mixture of ethylene carbonate (EC) and diethyl carbonate (DEC).

[0178] Preparation steps: First, add EC and DEC solvents to a dry, sealed container and stir until homogeneous. Then, slowly add LiPF6 lithium salt and stir at room temperature until completely dissolved to obtain a homogeneous basic electrolyte. Next, add FEC additive and ETPTA polymerization monomer in sequence and stir at low speed for 15 minutes until the system is homogeneous and transparent. Finally, accurately weigh and add AIBN thermal initiator and stir in the dark for 5 minutes until completely dissolved. The entire process is carried out in the dark and at low temperature to avoid premature polymerization and finally obtain a homogeneous, precipitation-free in-situ polymerization precursor solution.

[0179] After the soft-pack battery is filled with electrolyte, it is left to stand for half an hour and then cured at a constant temperature of 60°C for one hour.

[0180] The resulting pouch cell battery was formed at a charge / discharge rate of 0.1C for the first two weeks, and then at 0.5C (1C = 200mAh / g) starting from the third week. The battery underwent 100 charge / discharge cycles at 25℃. Performance and analysis: At 0.1C, the pouch cell battery's initial charge capacity was 248mAh / g, and its initial discharge capacity was 209mAh / g, with a charge / discharge capacity difference of 39mAh / g. At 0.5C, the initial discharge capacity was 192mAh / g, and after 100 cycles, the discharge capacity was 158.3mAh / g. Full-cell testing demonstrates that this composite cathode material is suitable for solid-state battery systems.

[0181] Comparative Example 1 With Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material, D1, was prepared by mixing O2 and LiCoO2 in a mass ratio of 5:95. Among them, Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0182] Steps 1 and 2: Same as in Example 2.

[0183] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 5:95. 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain composite cathode material -D1.

[0184] Electrochemical performance characterization: Same as in Example 2.

[0185] Test Results and Analysis: The 0.1C battery's initial charge capacity is 221 mAh / g, and its initial discharge capacity is 207 mAh / g, with a charge / discharge capacity difference of 17 mAh / g. The 0.5C battery's initial discharge specific capacity is 200 mAh / g, and after 100 cycles, the discharge capacity is 178 mAh / g, with a capacity retention rate of 89%. However, this graded electrode exhibits [further issues due to Li]... 0.6 Li 1.22 Ni 0.02 Co0.03 Mn 0.73 The O2 content is only 5wt%, which is too low to fully utilize the high lithium delithiation advantage of the high-lithiation material. Half-cell tests show that at 0.1C, it can only replenish the corresponding lithium loss of 17mAh / g in the first week, making it difficult to replenish the lithium consumption of the negative electrode when applied to a full-cell system. Furthermore, the electrode compaction density of the 20MPa roller press is 3.7g / cm³. 3 The difficulty in achieving high actual density lies in the fact that after mixing a small amount of high-lithium material with a large amount of LiCoO2, the overall capacity of the electrode is dominated by LCO, thus losing the application value of high-lithium manganese-based materials and failing to achieve both high capacity and cycle stability.

[0186] Full cell assembly: The negative electrode uses silicon-carbon material, and the positive electrode surface loading of the pouch cell is approximately 19 ± 0.5 mg / cm³. 2 The overall np ratio of the battery is 1.08. The full battery charge / discharge voltage range is 3.0-4.5V. The formation charge / discharge rate is 0.1C for the first two weeks, and 0.5C (1C=200mAh / g) from the third week onwards. The charge / discharge cycle count is 300 cycles, and the test temperature is 25℃.

[0187] Test performance and analysis: such as Figure 11 As shown, the first charge capacity of the pouch battery at 0.1C is 223mAh / g, and the first discharge capacity is 185mAh / g; Figure 10 As shown, the initial discharge capacity at 0.5C was 171 mAh / g, and the discharge capacity after 300 cycles was 147 mAh / g. The full-cell performance test results indicate that the discharge specific capacity is significantly lower than that of Example 2, mainly due to the Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The proportion of O2 is too low, making it difficult to provide sufficient lithium loss.

[0188] like Figure 7 As shown, Comparative Example 1 experienced thermal runaway earlier, with an exothermic initiation temperature T1 of approximately 87°C, while the highest thermal runaway temperature T3 was approximately 497°C; Figure 8 As shown, the T2 corresponding to the self-heating rate of the battery in Comparative Example 1 reaching 60℃ / min is 171℃.

[0189] Comparative Example 2 With Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material, D2, was prepared by mixing O2 and LiCoO2 in a mass ratio of 40:60. Among them, Li... 0.6 Li1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0190] Steps 1 and 2: Same as in Example 2.

[0191] Step 3: Li 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 40:60 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain the composite cathode material - D2.

[0192] Electrochemical performance characterization: Same as in Example 2, but the compaction density of the electrode sheet pressed by the 20MPa roller press was only 3.75 g / cm³. 3 .

[0193] Test Results and Analysis: The battery's initial charge capacity was 305 mAh / g, and its initial discharge capacity was 227 mAh / g, with a charge / discharge capacity difference of 78 mAh / g, indicating a relatively large initial irreversible capacity. After 100 cycles at 0.5C, the discharge capacity was 173 mAh / g, showing poor cycle performance. However, this graded electrode, due to Li... 0.6 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The O2 content is as high as 40 wt%, which significantly reduces the overall structural stability of the material. This is mainly because an excessively high proportion of high-lithium materials severely compromises the electrode's cycle stability, hindering practical applications.

[0194] Full cell assembly: The negative electrode uses silicon-carbon material, and the positive electrode surface loading of the pouch cell is approximately 19 ± 0.5 mg / cm³. 2 The overall np ratio of the battery is 1.08. The full battery charge / discharge voltage range is 3.0-4.5V. The formation charge / discharge rate is 0.1C for the first two weeks, and 0.5C (1C=200mAh / g) from the third week onwards. The charge / discharge cycle count is 300 cycles, and the test temperature is 25℃.

[0195] Test performance and analysis: such as Figure 10As shown, the first charge capacity of the soft-pack battery at 0.1C is 298mAh / g, and the first discharge capacity is 247mAh / g; the first week capacity at 0.5C is 229mAh / g, and the cycle capacity decays rapidly. After 100 cycles, the capacity is only 90mAh / g, and it cannot cycle to 300 cycles. The excessive lithium release in the first week leads to severe overcharging of the positive and negative electrodes during the battery charging and discharging process, which causes the material structure to age and deteriorate rapidly.

[0196] Comparative Example 3 With Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 A composite cathode material, D3, was prepared by mixing O2 and LiCoO2 at a mass ratio of 20:80. Among them, Li... 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0197] Step 1: Same as in Example 1.

[0198] Step 2: Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 20:80 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 are mixed to obtain the composite cathode material - D3.

[0199] Electrochemical performance characterization: Same as Comparative Example 1.

[0200] Full battery test, such as Figure 10 As shown, the pouch battery's initial charge capacity at 0.1C is 220 mAh / g, and its initial discharge capacity is 207 mAh / g. At 0.5C, the initial capacity is 200.5 mAh / g, but the capacity decays rapidly, with a discharge capacity of only 118 mAh / g after 100 cycles. The pre-lithiated negative electrode cell exhibits poor cycle performance and safety. Half-cell testing indicates that at 0.1C, it only replenishes 13 mAh / g of lithium loss in the first cycle, making it unsuitable for use in full-cell systems.

[0201] like Figure 7 As shown, Comparative Example 3 had the earliest thermal runaway time, with an exothermic initiation temperature T1 of approximately 80°C, while the highest thermal runaway temperature T3 was approximately 609°C; Figure 8As shown, the T2 corresponding to the self-heating rate of the battery in Comparative Example 3 reaching 60℃ / min is 160℃.

[0202] This comparative example directly mixes commercially available, conventionally stoichiometric small-particle lithium-rich materials (LRM) with lithium non-lithium excess with LCO, while employing existing negative electrode lithium replenishment technologies, such as spray-stabilized lithium powder (SLMP), to compensate for system lithium loss.

[0203] The experimental data above shows that the comparative example, which uses a composite cathode material combining non-lithium-rich manganese-based materials with high-voltage LCO, struggles to function as a lithium replenisher. Furthermore, issues such as interface compatibility and electrolyte stability remain significant, primarily manifested in the following ways: First, large initial irreversible capacity loss: during activation, some released lithium ions and oxygen cannot fully return to the crystal lattice during discharge, resulting in low initial coulombic efficiency. Second, voltage and capacity decay: the average discharge voltage continuously decreases during cycling, leading to rapid energy density decay. Third, poor rate performance: the conduction rate of lithium ions and electrons within the bulk phase of the lithium-rich manganese-based material is slow, resulting in significant performance degradation during high-current charge and discharge. In addition, the comparative example relies entirely on an external, expensive negative electrode lithium replenishment process, presenting challenges such as processing difficulty, safety risks, and high cost.

[0204] Comparative Example 4 Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 and LiCoO2 were graded in a mass ratio of 20:80, and sacrificial lithium supplementer Li5FeO4 was added in a mass ratio of 5:95 to the positive electrode active material to prepare the composite positive electrode material -D4. Among them, Li... 1.22 Ni 0.02 Co 0.03 Mn 0.73 O2 particles have a diameter of 2 μm and a purity of ≥99.5%; LiCoO2 particles have a diameter of 12 μm and a purity of ≥99.8%.

[0205] Step 1: Same as in Example 1.

[0206] Step 2: Li 1.22 Ni 0.02 Co 0.03 Mn 0.73 The combination of O2 and LiCoO2: Weigh Li according to a mass ratio of 20:80 1.22 Ni 0.02 Co 0.03 Mn 0.73O2 and LiCoO2 are mixed, and 5wt% of Li5FeO4 is added to obtain the composite cathode material -D4.

[0207] Electrochemical performance characterization: Based on the test conditions of Example 2, a gas detection device was used to monitor the gas generation during battery cycling.

[0208] Test Results and Analysis: After releasing lithium, Li5FeO4 transforms into electrochemically inert Fe2O3, becoming a persistent "dead mass" in the electrode and reducing the proportion of effective active material. Full cell testing is as follows... Figure 10 As shown, the pouch battery has an initial charge capacity of 240.5 mAh / g and an initial discharge capacity of 218 mAh / g at 0.1C; the difference between charge and discharge capacity is 22.5 mAh / g. At 0.5C, the initial discharge capacity is 197 mAh / g, but after 300 cycles, the discharge capacity is only 150 mAh / g. Compared to Example 2, it has the same discharge specific capacity, but the additional lithium replenishment and cycle life are significantly different. This comparative example has many shortcomings; compared to Example 2, its energy density continuously decreases.

[0209] In the comparative example, the sacrificial cathode lithium replenisher Li5FeO4 in the positive electrode transforms into electrochemically inert Fe2O3 and other substances after releasing lithium, becoming a persistent inactive material in the electrode and leading to a decrease in the system's energy density. Furthermore, this heterogeneous lithium replenisher may introduce new interfacial side reactions, exhibiting poor compatibility with LRM and LCO, and exacerbating gas generation or impedance growth. In addition, this comparative example also failed to solve the problems of low compaction density and severe side reactions caused by small-particle cathodes. The "lithium replenisher" of this invention transforms into a high-capacity active material after completing its lithium replenishment function, thereby continuously providing specific capacity and ensuring a high energy density for the system.

[0210] Comparative Example 5 Core-shell or gradient-doped composite positive materials - D5 1) Raw materials and reagents Lithium cobalt oxide (LCO): Same as in Example 1; Lithium-rich layer raw materials: LiNO3, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Mn(NO3)2·4H2O (all with a purity ≥99.5%); Binder, conductive agent, solvent, electrolyte, separator, and lithium metal sheet are all the same as in Example 1.

[0211] 2) A core-shell structured material with an LCO core and a lithium-rich coating was synthesized using a hydrothermal method. The specific preparation method is as follows: First, LCO particles are dispersed in deionized water, then lithium-rich layer raw materials are added and the pH is adjusted to 8-9. The mixture is then subjected to hydrothermal reaction at 180℃ for 12 hours. After cooling, the mixture is filtered, washed, and vacuum dried at 80℃ for 12 hours. Finally, it is calcined at 750℃ for 6 hours to obtain a core-shell structure material (LCO@lithium-rich layer) with a lithium-rich layer on its surface.

[0212] 3) Electrochemical performance characterization: Electrode preparation: Electrode slurry was prepared, coated, dried, pressed, and cut according to the process in Example 1. The active material loading of the electrode was 10 ± 0.5 mg / cm³. 2 The remaining process parameters are the same as in Example 1.

[0213] Battery assembly: Same as in Example 1.

[0214] Performance testing: Test conditions are the same as in Example 1. Test Results and Analysis: The battery's initial charge capacity was 230 mAh / g, and its initial discharge capacity was 198 mAh / g, with a charge-discharge capacity difference of 32 mAh / g. After 100 cycles at 0.5C, the discharge capacity retention rate was only 123 mAh / g, indicating a low discharge specific capacity. The manufacturing process was too difficult, and the instability of the LCO surface significantly reduced its performance.

[0215] The comparative synthesis method involves synthesizing a core-shell or gradient-doped structure material to obtain a single-particle material with an LCO core and a surface coated with or gradient-doped lithium-rich layers (or lithium-supplementing layers). This synthesis method is not only cumbersome and costly, but also presents challenges in designing the gradient surface of a single material, making it difficult to guarantee batch consistency and stability, thus hindering commercial application. Furthermore, precisely controlling the thickness and composition of the surface layer using this method is extremely difficult; under high-pressure cycling, the core-shell interface may become unstable, leading to coating peeling or failure. Simultaneously, the single-particle design makes it difficult to simultaneously optimize the compaction density of the core and the lithium-supplementing / high-capacity function of the shell, making it difficult to improve performance synchronously. In contrast, this invention flexibly and precisely controls the lithium-supplementing amount and electrode performance by adjusting the ratio of two independent materials.

[0216] In summary, the alternative solutions of ratios 3-5 can only solve some of the problems of the existing cathode system and will introduce new and more serious problems. The essence of this invention is to convert the traditionally "lost" lithium into an effective component for the construction of the SEI film on the anode, thereby significantly increasing the total amount of recyclable lithium that can participate in charge and discharge cycles. From the perspectives of overall technical effectiveness, ease of implementation, and commercial application, it has significant advantages.

[0217] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite cathode material containing high-lithium manganese-based materials, characterized in that, The composite cathode material includes: a high-lithium manganese-based material and a cathode active material; The chemical structural formula of the high-lithium manganese-based material is Li m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where m ranges from 0.2 to 1.1, x1 ranges from 0.1 to 0.3, m+x1 ranges from 0.5 to 1.2, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2; Among them, Li m The additional lithium-intercalated lithium-rich manganese-based host material Li represents the addition of lithium intercalation. 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2 occupies tetrahedral sites in the crystal lattice of the lithium-rich manganese-based host material; The high-lithium manganese-based material accounts for 10-30 wt% of the mass percentage of the composite cathode material; The high-lithium manganese-based material is used to release at least part of the Li during the first charge. m The additional lithium introduced is converted into an electrochemically active lithium-rich manganese-based material to continuously participate in reversible lithium insertion and delithiation reactions during subsequent charge-discharge cycles, and at least a portion of the released lithium is used to compensate for irreversible lithium loss during the first charge-discharge cycle of the battery.

2. The composite cathode material according to claim 1, characterized in that, In the chemical structural formula of the high-lithium manganese-based material, m ranges from 0.4 to 0.8, x1 ranges from 0.2 to 0.3, m+x1 ranges from 0.6 to 1.1, y1 ranges from 0.02 to 0.15, and z1 ranges from 0.03 to 0.

15. The high-lithium manganese-based material accounts for 15-25 wt% of the mass of the composite cathode material.

3. The composite cathode material according to claim 1, characterized in that, The high-lithium manganese-based material is: micron-sized pure phase particles with a single crystal structure of O2 phase and / or O3 phase and a median particle size D50 of 1 to 5 μm; The median particle size D50 of the positive electrode active material is 8–20 μm.

4. The composite cathode material according to claim 1, characterized in that, The positive electrode active material includes: LiCoO2, LiNi a Mn 2-a O4 or ternary material LiNi 1-x-y Co x M y One or more of O2; Among them, LiNi a Mn 2-a In O4, 0 ≤ a ≤ 0.5; LiNi 1-x-y Co x M y In O2, M is either Mn or Al, 0 < x < 0.5, 0 < y < 0.5, and x + y ≤ 0.

5.

5. A method for preparing the composite cathode material according to any one of claims 1-4, characterized in that, The preparation method includes: Preparation or preparation of lithium-rich manganese-based materials Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where x1 ranges from 0.1 to 0.3, y1 ranges from 0.01 to 0.2, and z1 ranges from 0.03 to 0.2; Lithium supplementation is performed on the lithium-rich manganese-based material to obtain a high-lithium manganese-based material, Li. m Li 1+x1 Ni y1 Co z1 Mn 1-x1-y1-z1 O2; where m ranges from 0.2 to 1.1, and m+x1 ranges from 0.5 to 1.2; The high-lithium manganese-based material is mixed with the positive electrode active material to obtain the composite positive electrode material.

6. The preparation method according to claim 5, characterized in that, The methods for preparing the lithium-rich manganese-based material include one or more of the following: ion exchange method, coprecipitation method, sol-gel method, solid phase method, hydrothermal method, spray drying method, or combustion method.

7. The preparation method according to claim 5, characterized in that, The specific steps of replenishing lithium in the lithium-rich manganese-based material include: Under an inert atmosphere, weigh out 0.01–0.1 mol / L of lithium replenishment promoter and dissolve it in a solvent. After stirring and dissolving, a clear solution is formed. Based on the amount of lithium-rich manganese-based material to be lithium-replenished and the target lithium replenishment amount m, metallic lithium is added to the clarified solution and stirred continuously to allow the metallic lithium to react with the lithium replenishment promoter and form a lithium-containing complex, thereby obtaining a lithium-replenishing solution; wherein, the amount of metallic lithium is not less than the theoretical stoichiometry required to replenish the lithium-rich manganese-based material to the target lithium replenishment amount m. The lithium-rich manganese-based material to be replenished with lithium is added to the lithium replenishment solution, and the reaction is carried out under an inert atmosphere. After the reaction is completed, the solid product is separated, washed and dried to obtain the high-lithium manganese-based material.

8. The preparation method according to claim 5, characterized in that, The lithium supplementation promoter includes one or more of 9-fluorenone, pyrene, and biphenyl; The lithium replenishment promoter includes: a single lithium replenishment promoter, or a composite lithium replenishment promoter; The lithium complex formed by the single lithium supplementation promoter has a moderate HOMO energy level; the moderate HOMO energy level is -3.5 eV to -2.5 eV, preferably -3.2 eV to -3.0 eV; The composite lithium replenishment promoter includes at least two lithium replenishment promoters, namely a strong lithium replenishment promoter and a weak lithium replenishment promoter; the lithium complex formed by the strong lithium replenishment promoter and lithium has a relatively high HOMO energy level, -3.0 eV ≤ E HOMO ≤-2.2eV; the lithium complex formed by the weak lithium-compensating promoter and lithium has a relatively low HOMO energy level, -3.7eV≤E HOMO <-3.0eV; In the composite lithium supplementation accelerator, the molar ratio of the strong lithium supplementation accelerator to the weak lithium supplementation accelerator is 1:1-20.

9. An electrode sheet, characterized in that, The electrode comprises: the composite cathode material according to any one of claims 1-4, or the composite cathode material obtained by the preparation method according to any one of claims 5-8.

10. A lithium battery, characterized in that, The lithium battery comprises: the composite cathode material according to any one of claims 1-4, or the composite cathode material obtained by the preparation method according to any one of claims 5-8, or the electrode sheet according to claim 9; Preferably, the lithium battery includes one or more of the following: liquid lithium-ion battery, liquid metal lithium battery, hybrid solid-liquid lithium-ion battery, hybrid solid-liquid metal lithium battery, in-situ solidified lithium battery, solid lithium-ion battery, or solid metal lithium battery.